Guides for value-chain development: A comparative review - Donovan, Jason; Franzel, Steven; Cunha, Marcelo; Gyau, Amos; Mithöfer, Dagmar (International Food Policy Research Institute, 2016)
This chapter reviews 11 guides for value-chain analysis and development. It compares the guides’ concepts, objectives, and methods and identifies strengths, weaknesses, and gaps. The assessment characterizes the state of the art for designing interventions and interactions that seek to build value chains with smallholders. The chapter is organized as follows: presents the methodology applied in carrying out the review, the following section presents the results of this review, and the final section provides concluding comments.